Romania - Functional Review : Environment, Water and Forestry, Volume 1. Main Report - World Bank (Washington, DC, 2013)
The objective of the Functional Review of the Environment, Water and Forestry sector (FR-EWF) is to help the Government of Romania (GoR) develop an action plan for implementation over the short- and medium-term to strengthen the effectiveness and efficiency of the sector administration, and provide input to the Government National Reform Program (NRP 2011- 2013) and beyond, especially in relation to those functions that support Romania's implementation of key EU directives, help speed up convergence with the environmental Acquis, remove constraints to EU structural funds absorption, and manage the country's natural assets sustainably. The report is presented in two volumes, with the first volume providing an integrated view of the sector as currently configured around environmental management, water, and forestry, and the second volume dedicated to a detailed review of the forestry sector. Volume 1 is organized as follows: Part I provides an overall introduction, objectives and context of the review; Part II summarizes the key challenges facing the sector, focusing on the three main sub-sectors, environmental management, water, and forestry; Part III reviews the strategic framework of the sector, pointing out areas where improvements will be needed; Part IV reviews the configuration of the sector, its organization and performance; Part V assesses the salient cross-cutting issues; and Part VI presents the key recommendations. Volume 2, dedicated to the forestry sub-sector, is organized along the four assessment areas.